2014
DOI: 10.1103/physrevlett.113.044502
|View full text |Cite
|
Sign up to set email alerts
|

Dense Suspension Splat: Monolayer Spreading and Hole Formation after Impact

Abstract: We use experiments and minimal numerical models to investigate the rapidly expanding monolayer formed by the impact of a dense suspension drop against a smooth solid surface. The expansion creates a lace-like pattern of particle clusters separated by particle-free regions. Both the expansion and the development of the spatial inhomogeneity are dominated by particle inertia, therefore robust and insensitive to details of the surface wetting, capillarity and viscous drag.PACS numbers: 82.70. Kj, 45.70.Qj, 82.70.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…In this situation, the thickness of the liquid film can become comparable to the particle size and the displacement of a particle will be controlled by the drag force exerted by the fluid and the capillary force due to the air/liquid interface deformation. [41,42] Capillary effects are important when interfaces confine particles. [43] Recent studies have shown the influence of particles on the detachment of droplets from a jet of suspension, [44,45,46] which has important industrial applications, including printing.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, the thickness of the liquid film can become comparable to the particle size and the displacement of a particle will be controlled by the drag force exerted by the fluid and the capillary force due to the air/liquid interface deformation. [41,42] Capillary effects are important when interfaces confine particles. [43] Recent studies have shown the influence of particles on the detachment of droplets from a jet of suspension, [44,45,46] which has important industrial applications, including printing.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the modification of the spreading dynamics is an intrinsic local effect of the particles. Qualitatively, the presence of particles larger than the thickness of the sheet creates a deformation of the interface that limits its expansion and dynamics [11]. During the spreading and the fragmentation of the particleladen liquid sheet, droplets are generated from two different ways.…”
Section: Spreading Of Particle-laden Liquid Sheetsmentioning
confidence: 99%
“…We did not notice a significant change in droplet size for Newtonian fluid with similar viscosities. Therefore, the influence of the particles goes beyond the increase in viscosity of the suspension, modifying the generation process of the droplets compared to a classical Newtonian liquid [11].…”
Section: Spreading Of Particle-laden Liquid Sheetsmentioning
confidence: 99%
“…[3][4][5] While signicant fundamental research has focused on the hydrodynamic instabilities of a homogeneous uid experiencing dripping, 6 splashing, 7,8 and dewetting, 9 the understanding of the coupling between the ow dynamics and solidication is still in its infancy. [3][4][5] While signicant fundamental research has focused on the hydrodynamic instabilities of a homogeneous uid experiencing dripping, 6 splashing, 7,8 and dewetting, 9 the understanding of the coupling between the ow dynamics and solidication is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%